Pro android 5 - Maclean, Dave (Apress, 2015)
Pro Android 5 shows you how to build real-world and fun mobile apps using the Android 5 SDK. This book updates the best-selling Pro Android and covers everything from the fundamentals of building apps for smartphones, tablets, and embedded devices to advanced concepts such as custom components, multi-tasking, sensors/augmented reality, better accessories support and much more.